Outcome of premature thelarche: relation to puberty and final height. Issue 2 (1st August 1998) - Salardi, S; Cacciari, E; Mainetti, B; Mazzanti, L; Pirazzoli, P
Abstract : BACKGROUND: There is a debate about the possible progression of idiopathic premature thelarche towards precocious or early puberty. OBJECTIVE: To evaluate height and age at onset of puberty in a group of girls with a history of idiopathic premature thelarche. STUDY DESIGN: The height and age at onset of puberty of 42 girls now over 10 years of age who were diagnosed with isolated premature thelarche before the age of 3 years were evaluated. RESULTS: Menarche was reached before or at 11 years of age in 13.5% of this group of girls. This percentage of early menarche was higher than would be expected from historical controls in the general population, but was consistent with maternal age of menarche. The mean (SD) height of the girls (n = 15) who achieved adult height was 162.9 (6.3) cm, which was slightly higher than the mean (SD) relative midparental height (160.7 (6.7) cm). CONCLUSIONS: Isolated premature thelarche with onset before 3 years of age progresses towards precocious puberty, although this was consistent with the maternal age of menarche. Furthermore, adult height was normal when compared with population norms in all patients.